2019
DOI: 10.1093/mnras/stz2504
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the shadows of giants: characterizing protoclusters with line of sight Lyman-α absorption

Abstract: We use state of the art hydrodyamical simulations from the Sherwood, EAGLE and Illustris projects to examine the signature of M z=0 10 14 M protoclusters observed in Ly-α absorption at z 2.4. We find there is a weak correlation between the mass overdensity, δ m , and the Ly-α effective optical depth relative to the mean, δ τ eff , averaged over 15 h −1 cMpc scales, although scatter in the δ m -δ τ eff plane means it is not possible to uniquely identify large scale overdensities with strong Ly-α absorption. Alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 84 publications
(120 reference statements)
3
15
0
Order By: Relevance
“…The transmission contrast of this spatial offset is further enhanced by the proximity effect associated with a M 1450 = −24.7 AGN hosted within the halo. We furthermore find that the incidence of CoSLAs within protoclusters is sensitive to changes in our local ionization models, largely as a result of changes in the number of self-shielded, damped Ly α absorbers with N H I ≥ 10 19 cm −2 (see also Miller et al 2019).…”
Section: Protocluster Masses and The Correlation Between Laes And Ly α Transmission In Smoothed Mapsmentioning
confidence: 77%
See 2 more Smart Citations
“…The transmission contrast of this spatial offset is further enhanced by the proximity effect associated with a M 1450 = −24.7 AGN hosted within the halo. We furthermore find that the incidence of CoSLAs within protoclusters is sensitive to changes in our local ionization models, largely as a result of changes in the number of self-shielded, damped Ly α absorbers with N H I ≥ 10 19 cm −2 (see also Miller et al 2019).…”
Section: Protocluster Masses and The Correlation Between Laes And Ly α Transmission In Smoothed Mapsmentioning
confidence: 77%
“…In particular, the dynamic range of the hydrodynamical simulations should ideally be larger. A mass resolution of M gas ∼ 10 6 M is required to resolve Ly α absorption from the IGM at z 2 (Bolton & Becker 2009;Miller et al 2019). While the Ly α forest in the TNG100-1 simulation is therefore well resolved, the statistics are somewhat limited with only 22 protoclusters with M z=0 ≥ 10 14 M .…”
Section: Protocluster Masses and The Correlation Between Laes And Ly α Transmission In Smoothed Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray and mm-wavelength observations -the latter via the Sunyaev-Zel'dovich effect (Sunyaev & Zeldovich 1972) -are used to identify the 𝑇 ∼ 10 7 K intracluster medium within massive collapsed clusters and groups (Ebeling et al 2010;Finoguenov et al 2010;Bleem et al 2015), leading to the detection of clusters up to redshifts of 𝑧 = 1.7 (Strazzullo et al 2019). Yet the majority of the gas by volume within protoclusters has not yet been shock heated to X-ray emitting temperatures and instead has 𝑇 ∼ 10 4 K (Miller et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Cai et al (2017) have used spectral regions with strong Ly-𝛼 transmission decrements over a scale of 15ℎ −1 cMpc -which they name Coherently Strong Ly𝛼 Absorption systems (CoSLAs) -to locate a protocluster at 𝑧 = 2.3 (see also Cai et al 2016;Zheng et al 2021;Shi et al 2021). However, using cosmological hydrodynamical simulations, Miller et al (2019) (hereafter Paper I) also showed that such CoSLAs are rare 1 and are not an exclusive probe of protoclusters. It is possible to adopt a rather strict (and model dependent) CoSLA detection threshold that removes contamination from coherent structures originating in the diffuse IGM, but any such protocluster sample is then incomplete.…”
Section: Introductionmentioning
confidence: 99%